Reproductive biology of Psammobatis rutrum (Chondrichthyes: Arhynchobatidae) in south Brazil, south-west Atlantic - Martins, M. F. [UNESP]; Oddone, M. C. (Wiley-Blackwell, 2017)
This study presents information on the reproductive biology of Psammobatis rutrum based on 55 males and 53 females obtained as by-catch from bottom trawlers off southern Brazil during July 2013 and September 2014 and includes a detailed description of the egg capsule. Total lengths (L-T) ranged from 223 to 316cm and most of the sample comprised larger individuals, although there were no sexual differences in length-frequency distributions. Significant sexual differences were found for total length-disc width, L-T-body mass and L-T-eviscerated body mass relationships, with females being heavier and larger. Males started to mature at 255cm L-T and females, at 259cm L-T, while L-T at maturity was calculated in 2667 and 2681cm, respectively. Attaining larger sizes and mass may represent a reproductive investment for females, as observed in other rajoid species. Egg bearing females were first observed over 271cm L-T and ovarian fecundity was 1-12 vitellogenic follicles. The egg capsules were 222-262cm length and had attaching fibrils on both lateral sides. Microscopically, the ventral face of the egg capsule was rougher than the dorsal face.
Keywords: clasper; egg capsule; fecundity; morphometrics; oviparity; size at maturity